2019
DOI: 10.3892/etm.2019.8239
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes in the endothelial precursor cells of patients with type 2 diabetes mellitus by bioinformatics analysis

Abstract: Type 2 diabetes mellitus (DM) is a metabolic disease with worldwide prevalence that is associated with a decrease in the number and function of endothelial progenitor cells (EPCs). The aim of the present study was to explore the potential hub genes of EPCs in patients with type 2 DM. Differentially expressed genes (DEGs) were screened from a public microarray dataset (accession no. GSE43950). Pathway and functional enrichment analyses were performed using the Database for Annotation, Visualization and Integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Other studies showed elevated circulating IL-8 levels in T2DM patients [193]. A bioinformatic analysis in endothelial precursor cells isolated from patients with T2DM showed that IL-8 and CXCL1 genes were the most expressed molecules in diabetic samples [196].…”
Section: Other Cytokines/proinflammatory Proteins In Dnmentioning
confidence: 95%
“…Other studies showed elevated circulating IL-8 levels in T2DM patients [193]. A bioinformatic analysis in endothelial precursor cells isolated from patients with T2DM showed that IL-8 and CXCL1 genes were the most expressed molecules in diabetic samples [196].…”
Section: Other Cytokines/proinflammatory Proteins In Dnmentioning
confidence: 95%
“…We completed the network topology analysis with a threshold power ranging from 1 to 20. When the power value was equal to 7 (scale-free R 2 = 0:9) [21], our record showed a scale-free gene coexpression network with complete module characteristics. The cluster tree structure of the topology overlap matrix was constructed.…”
Section: Gene Coexpression Network Of T2dmmentioning
confidence: 84%
“…Weighted correlation network analysis (WGCNA) is a systems biology method to describe the correlation patterns between genes across microarray samples, which is used to find highly related gene modules and calculate module membership to identify candidate biomarkers or 2 BioMed Research International therapeutic targets [20]. This algorithm has been widely used to identify biomarkers at the transcriptional level [21][22][23]. In this study, microarray data from public databases were subjected to WGCNA, and a coexpression network was constructed to screen differential genes between patients with T2DM and healthy people.…”
Section: Introductionmentioning
confidence: 99%
“…The gene network and pathways were analysed using DAVID v6.8 for GO enrichment analysis with Benjamini significant P < 0.05 for both up鈥恟egulated and down鈥恟egulated genes. The Gene interaction network construction and visualization was performed using Cytoscape v3.8.2 29,30 . The identified treatment responsive differentially expressed genes were created with the Search Tool for the Retrieval of Interacting Genes and proteins (STRING) database.…”
Section: Methodsmentioning
confidence: 99%